2012
DOI: 10.1111/j.1440-1746.2011.07057.x
|View full text |Cite
|
Sign up to set email alerts
|

CD14 expression and Kupffer cell dysfunction in non‐alcoholic steatohepatitis: Superparamagnetic iron oxide‐magnetic resonance image and pathologic correlation

Abstract: KC phagocytic function evaluated with SPIO-MRI correlated with histopathological severity and number of CD14-positive KCs. These results support the concept that KC phagocytic dysfunction contributes to the pathogenesis of NASH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…has shown that inheritance of the 2518 MCP-1 G allele predisposes patients infected with the hepatitis C virus to more severe hepatic inflammation and fibrosis. Finally, Tonan et al 62. reported that Kupffer cell dysfunction contributes to the pathogenesis of non-alcoholic steatohepatitis, as CD14-positive Kupffer cells increase along with increase in necroinflammation grade and fibrosis stage.…”
Section: Immunological Dysfunction In Cirrhosismentioning
confidence: 99%
“…has shown that inheritance of the 2518 MCP-1 G allele predisposes patients infected with the hepatitis C virus to more severe hepatic inflammation and fibrosis. Finally, Tonan et al 62. reported that Kupffer cell dysfunction contributes to the pathogenesis of non-alcoholic steatohepatitis, as CD14-positive Kupffer cells increase along with increase in necroinflammation grade and fibrosis stage.…”
Section: Immunological Dysfunction In Cirrhosismentioning
confidence: 99%
“…17 In contrast to USPIO, SPIONs are characterized by enhanced liver accumulation, thereby constituting a superb hepatic MRI contrast agent. Low concentrations of SPIONs (0.5 mg Fe/kg of carboxydextran-coated ferucarbotran (Resovist/Ferrixan, 45-60 nm [18][19][20], or dextran-coated ferumoxides (Endorem/Feridex), 21 have been used to noninvasively distinguish between benign liver condition (simple steatosis) and nonalcoholic steatohepatitis (NASH), which is highly associated with cardiovascular and renal comorbidities. 22 Despite promising results in humans, the marketing of intravenous iron oxide-containing contrast agents is currently at a standstill.…”
Section: Introductionmentioning
confidence: 99%
“…5B and C. The peak enhancement in T 2 -weighted MRI of normal liver parenchyma could be obtained at 30 min post the injection of Fe 3 O 4 -Au NPs, which was significantly later than that of the normal rats. We speculated that the time delay to the phagocytosis dysfunction was caused by liver cirrhosis [54]. On this basis, a much faster washout of Fe 3 O 4 -Au NPs could be observed with respect to that of normal rats (washout rate represented with MR signal intensity reduction estimated with R2 48h /R2 30min, ca.…”
Section: Mr and Ct Measurements In Cirrhotic Livermentioning
confidence: 97%